Co‐Assembly Induced Solid‐State Stacking Transformation in Amino Acid‐Based Crystals with Enhanced Physical Properties. Issue 17 (2nd March 2022) - Ji, Wei; Yuan, Hui; Xue, Bin; Guerin, Sarah; Li, Hui; Zhang, Lei; Liu, Yanqing; Shimon, Linda J. W.; Si, Mingsu; Cao, Yi; Wang, Wei; Thompson, Damien; et al.
Abstract: The physical characteristics of supramolecular assemblies composed of small building blocks are dictated by molecular packing patterns in the solid‐state. Yet, the structure–property correlation is still not fully understood. Herein, we report the unexpected cofacial to herringbone stacking transformation of a small aromatic bipyridine through co‐assembly with acetylated glutamic acid. The unique solid‐state structural transformation results in enhanced physical properties of the supramolecular organizations. The co‐assembly methodology was further expanded to obtain diverse molecular packings by different bipyridine and acetylated amino acid derivatives. This study presents a feasible co‐assembly approach to achieve the solid‐state stacking transformation of supramolecular organization and opens up new opportunities to further explore the relationship between molecular arrangement and properties of supramolecular assemblies by crystal engineering. Abstract : This study reports co‐assembly induced solid‐state cofacial to herringbone stacking transformation, as validated by X‐ray crystallography, using very simple molecular building blocks. The stacking transformation resulted in modulation of the physical properties of the supramolecular organizations, which promotes the precise understanding of the relationship between molecular packing and properties of supramolecular assemblies.